Kajian Ekstraksi Antosianin dari Buah Murbei dengan Metode Sonikasi dan Microwave - Anitarakhmi Handaratri; Yuyun Yuniati (Universitas Tribhuwana Tunggadewi Malang, 2019)
The pigment in mulberry (Morus alba L.), anthocyanin, is a kind of natural pigment for food processing and has functional potential and commercial values. Some investigators have developed a method to obtain high extraction yields in a short time. High yields with Ultrasonic Assisted Extraction method using ultrasonic waves that affect the cell wall and causes the destruction of a thin layer and helps in releasing phenolic compounds that trapped in the cell wall. Microwave Assisted Extraction method uses the energy of microwave radiation to heat the solvent quickly and efficiently. This study concludes and gives an overview advantages of both methods were compared with conventional methods.